To find the zeros of the quadratic equation \( y = -3x^2 + 12x + 15 \), we can use the quadratic formula, which is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
In the given equation, the coefficients are as follows:
- \( a = -3 \)
- \( b = 12 \)
- \( c = 15 \)
First, we need to compute the discriminant (\( b^2 - 4ac \)):
\[ b^2 - 4ac = 12^2 - 4(-3)(15) \] \[ = 144 + 180 \] \[ = 324 \]
Since the discriminant is positive, we have two real and distinct solutions. Now we can substitute the values into the quadratic formula:
\[ x = \frac{-12 \pm \sqrt{324}}{2(-3)} \]
Calculating \( \sqrt{324} \):
\[ \sqrt{324} = 18 \]
Now substituting back into the formula:
\[ x = \frac{-12 \pm 18}{-6} \]
This gives us two cases to solve:
- \( x = \frac{-12 + 18}{-6} = \frac{6}{-6} = -1 \)
- \( x = \frac{-12 - 18}{-6} = \frac{-30}{-6} = 5 \)
Thus, the zeros of the equation \( y = -3x^2 + 12x + 15 \) are:
\[ x = -1 \quad \text{and} \quad x = 5 \]
So, the zeros of the quadratic function are \( x = -1 \) and \( x = 5 \).